PENGARUH UTANG, PROFITABILITAS, DAN NILAI PASAR TERHADAP RETURN SAHAM SEKTOR CONSUMER NON-CYCLICALS DI BEI - Rahmayanti, Felia; Suherman, Suherman; Hamidah, Hamidah (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to determine the effect of debt proxied by Debt-to-Equity Ratio (DER), profitability proxied by Return on Equity (ROE), and market value proxied by Price to Book Value (PBV) on stock returns, either by using control variables with firm size and sales growth or without using control variables. The research sample was taken using a purposive sampling technique, covering 55 companies in the consumer non-cyclicals sector on the IDX for the 2019-2022 period (220 observations). This study uses secondary data from annual reports. The analysis technique used was panel data regression with Fixed Effect Model approach using Eviews 12 software. The results show that DER has a significant negative influence on stock returns, ROE has no effect on stock returns, and PBV has a significant positive influence on stock returns